Ultra-small PbS nanocrystals as sensitizers for red-to-blue triplet-fusion upconversion. Issue 42 (11th October 2021) - Imperiale, Christian J.; Green, Philippe B.; Hasham, Minhal; Wilson, Mark W. B.
Abstract : We demonstrate the use of ultra-small PbS quantum dots as endothermic sensitizers for red-to-blue triplet-fusion upconversion, achieving nanocrystal-sensitized upconversion photochemistry. Abstract : Photon upconversion is a strategy to generate high-energy excitations from low-energy photon input, enabling advanced architectures for imaging and photochemistry. Here, we show that ultra-small PbS nanocrystals can sensitize red-to-blue triplet-fusion upconversion with a large anti-Stokes shift (Δ E = 1.04 eV), and achieve max-efficiency upconversion at near-solar fluences ( I th = 220 mW cm −2 ) despite endothermic triplet sensitization. This system facilitates the photo-initiated polymerization of methyl methacrylate using only long-wavelength light ( λ exc : 637 nm); a demonstration of nanocrystal-sensitized upconversion photochemistry. Time-resolved spectroscopy and kinetic modelling clarify key loss channels, highlighting the benefit of long-lifetime nanocrystal sensitizers, but revealing that many (48%) excitons that reach triplet-extracting carboxyphenylanthracene ligands decay before they can transfer to free-floating acceptors—emphasizing the need to address the reduced lifetimes that we determine for molecular triplets near the nanocrystal surface. Finally, we find that the inferred thermodynamics of triplet sensitization from these ultra-small PbS quantum dots are surprisingly favourable—completing an advantageous suite of properties for upconversion photochemistry—and do not vary significantly across the ensemble, which indicates minimal effects from nanocrystal heterogeneity. Together, our demonstration and study of red-to-blue upconversion using ultra-small PbS nanocrystals in a quasi-equilibrium, mildly endothermic sensitization scheme offer design rules to advance implementations of triplet fusion, especially where large anti-Stokes wavelength shifts are sought.